Childhood Trauma and COMT Genotype Interact to Increase Hippocampal Activation in Resilient Individuals - van Rooij, Sanne J. H.; Stevens, Jennifer S.; Ely, Timothy D.; Fani, Negar; Smith, Alicia K.; Kerley, Kimberly A.; Lori, Adriana; Ressler, Kerry J.; Jovanovic, Tanja (Frontiers in Psychiatry, 2016)
Both childhood trauma and a functional COMT genetic polymorphism have been associated with PTSD and depression; however, it is still unclear whether the two interact and how this interaction relates to long-term risk or resilience. Imaging and genotype data were collected on 73 highly traumatized women. DNA extracted from saliva was used to determine COMT genotype (Val/Val, n=38, Met carriers, n=35). Functional MRI data were collected during a Go/NoGo task to investigate the neurocircuitry underlying response inhibition. Self-report measures of adult and childhood trauma exposure, PTSD and depression symptom severity, and resilience were collected. Childhood trauma was found to interact with COMT genotype to impact inhibition-related hippocampal activation. In Met carriers, more childhood trauma was associated with decreased hippocampal activation, whereas in the Val/Val group childhood trauma was related to increased hippocampal activation. Second, hippocampal activation correlated negatively with PTSD and depression symptoms, and positively with trait resilience. Moreover, hippocampal activation mediated the relationship between childhood trauma and psychiatric risk or resilience in the Val/Val, but not in the Met-carrier group. These data reveal a potential mechanism by which childhood trauma and COMT genotype interact to increase risk for trauma-related psychopathology or resilience. Hippocampal recruitment during inhibition may improve the ability to use contextual information to guide behavior, thereby enhancing resilience in trauma-exposed individuals. This finding may contribute to early identification of individuals at risk, and suggests a mechanism that can be targeted in future studies aiming to prevent or limit negative outcomes.